Revitalizing the Islamic Economic System: from Theory to Action to Reduce Social Inequality and Improve Community Welfare - Ekawaty, Marlina (Arbain Publishing, 2025)
Social inequality remains a persistent challenge in many Muslim-majority countries, despite the existence of Islamic economic principles that emphasize justice, inclusivity, and welfare distribution. This study aims to evaluate the application of Islamic economic values in real policy implementations and their impact on marginalized communities. Using the Systematic Literature Review (SLR) method guided by the PRISMA protocol, a total of 425 initial records from reputable databases were screened, resulting in 20 eligible articles for in-depth analysis. The findings indicate that the integration of Islamic social finance instruments—such as zakat, waqf, and qard al-hasan—alongside innovative financing models and targeted mentoring programs, significantly improves both material and spiritual welfare indicators among low-income groups. Evidence from multiple empirical studies suggests that religious framing, cost reduction, and strong community engagement enhance participation and program effectiveness. However, challenges such as governance quality, limited social participation outcomes, and weak integration with broader economic policies still limit long-term impact. The review concludes that revitalizing the Islamic economic system requires a holistic and context-sensitive approach, aligning financial instruments with capacity building, digital innovation, and policy integration to effectively reduce inequality and foster sustainable welfare.